2004
DOI: 10.2166/wst.2004.0018
|View full text |Cite
|
Sign up to set email alerts
|

Waterborne gastroenteritis outbreak in Albania

Abstract: Three different studies are reported concerning the environmental pollution caused by viruses in Albania. The first study describes an outbreak of gastroenteritis in the capital city, involving 2,722 children attending the Paediatric Unit of Tirana Hospital. The age group with the highest morbidity was 0-5 years, with 89.5%; no fatalities were recorded during the outbreak. Rotavirus was detected in 26/28 faecal samples by RT-PCR, although astrovirus, adenovirus and calicivirus were also present. The second stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 47 publications
(29 citation statements)
references
References 24 publications
0
28
0
1
Order By: Relevance
“…These findings indicate the gastroenteritis burden of pathogenic viruses present in the water, due to the use of river water for drinking or due to other routes of transmission, such as poor hygiene, lack of sanitation, or even contamination due to recreational activities such as bathing in these areas. Studies showing viral diarrheal illness due to waterborne transmission related to poor water quality have been documented, including the ingestion of contaminated water during body contact recreation (22,26,31,38,52). In addition, the detection and characterization of HAdV, RV, HAstV, and NoV in environmental water samples may provide potentially useful data for epidemiological studies.…”
Section: Vol 74 2008 Gastroenteritis Viruses In the Water Streams Omentioning
confidence: 99%
“…These findings indicate the gastroenteritis burden of pathogenic viruses present in the water, due to the use of river water for drinking or due to other routes of transmission, such as poor hygiene, lack of sanitation, or even contamination due to recreational activities such as bathing in these areas. Studies showing viral diarrheal illness due to waterborne transmission related to poor water quality have been documented, including the ingestion of contaminated water during body contact recreation (22,26,31,38,52). In addition, the detection and characterization of HAdV, RV, HAstV, and NoV in environmental water samples may provide potentially useful data for epidemiological studies.…”
Section: Vol 74 2008 Gastroenteritis Viruses In the Water Streams Omentioning
confidence: 99%
“…Outbreaks of viral acute gastroenteritis by consumption of contaminated water have been frequently reported in the world, and viruses are known as the etiological agents for the infectious gastroenteritis (Divizia et al 2004). While rotaviruses, astrovirus, and norovirus have been involved in these outbreaks (Hung et al 1984;Boccia et al 2002;Divizia et al 2004;Hoebe et al 2004;Gallay et al 2006;Hewitt et al 2007;Martinelli et al 2007;Maunula et al 2009), routine procedures for monitoring these viruses in water samples had not been drawn up for the water-microbiology screening panel. Sewage water contains much higher numbers of viruses (Meleg et al 2006) and sewage workers frequently exposed to raw sewage were found to be at higher risk of intestinal disease (Rylander 1999;Venczel et al 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Causes of diarrhoea include a wide array of bacteria, viruses and protozoa. Recent studies on microbiological and virological environmental pollution identified the quality of drinking water as a major health problem in the suburbs of the Albanian capital [3][4][5]. Among protozoan parasites, Giardia duodenalis is recognised as one of the most important non-viral infectious agent causing diarrhoeal illness in humans world-wide [6,7].…”
mentioning
confidence: 99%